Simultaneous determination of seven endogenous aldehydes in human blood by headspace gas chromatography–mass spectrometry - Wei, Yi; Wang, Menghan; Liu, Huixia; Niu, Ying; Wang, Shaomin; Zhang, Fuyi; Liu, Hongmin (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2019)
Endogenous aldehydes (EAs) formed by the free-radical-mediated reaction are regarded as potential biological markers of several diseases. In this work, an automated and solvent-free analytical method was developed for quantitative analysis of seven EAs (C1–C7) in human blood by using gas chromatography–mass spectrometry coupled with a headspace generator sampler (HS-GC–MS). A 1:4 (blood:water) dilution and the 1,2‑dibromopropane internal standard were introduced to reduce the influence of the matrix effect from complex biological fluids. The sample preparation steps were simplified. Various experimental parameters for derivatization and extraction conditions were studied such as HS extraction temperature and time, the amount of derivatization reagent, pH and the salt effect. Under these optimum conditions, seven low-mass aldehydes were separated and analyzed within 10 min. Additionally, this method achieved limits of detection in the range of 0.0692–0.864 μg/L, an excellent linearity with correlation coefficients higher than 0.9996 and appropriate repeatability and reproducibility values (RSD < 12% at low, middle and high levels). The HS-GC–MS method was applied to measure the concentrations of the seven aldehydes in blood from bladder cancer patients (n = 15) and control subjects (n = 15). Compared with the control subjects, the levels of butanal (p < 0.01), formaldehyde, acetaldehyde, propanal, pentanal, hexanal and heptanal (all p < 0.001) were increased significantly, indicating that EAs may be useful as biomarkers in the early diagnosis of bladder cancer. •HS-GC–MS for determination of seven aldehydes in human blood.•Simple, automatic and environmentally friendly method.•Aldehydes were detected with good accuracy in human blood.•Internal calibration for quantification of aldehydes in diluted blank blood.•Higher concentrations of aldehydes were detected in the blood of bladder cancer patients than in the blood of control subjects.